The Religiosity of Japanese Engineering Student Case Study At Toyohashi University of Technology - Nindhia, Tjokorda Gde Tirta (Makara Human Behavior Studies in Asia, 2007)
This article is intended to inform a real description related to the religious expression and activity of engineering student in Japan. Information is collected by direct interaction with the students, and also by visiting religious sites around the campus. Visit to the student apartments is also carried out to obtain information regarding religious activity that is held in daily life. It is found from the observation that religious activities such as reading a holy book and praying is not carried out anymore. Praying is done three times a year, namely at Bon ceremony, which is ceremony to respect the return ancestor to the earth from heaven, at Higan ceremony that is ceremony to respect the ancestor, and also new year praying. It is found surprisingly, something unique related to the religion that is many students have and bring amulet (o-mamori) that is obtained from the Shinto shrine or Buddhist temple. It is also popular to take a written oracle that tells the fortune in the Buddhist Temple or Shinto Shrine. This written oracle in Japan is called with o-mikuji. The belief that is not related to the religion but still popular is to respect the mountain. Mountain climbing is a religious activity that often held by the engineering student